Kontribusi Usahatani Cengkeh Terhadap Pendapatan Rumah Tangga Di Desa Saibuah Kecamatan Posigadan Kabupaten Bolaang Mongondow Selatan - Moh Syarif Abd Thaib; Herwin Mopangga; Irawati Abdul (As-Syirkah: Islamic Economic & Financial Journal, 2025)
The purpose of this study was to determine, (1) how much income from clove farming to the income of farmer households in saibuah village, posigadan district, south bolaang mongondow regency, (2) how much contribution clove farming to the income of farmer households in saibuah village, posigadan district, south bolaang mongondow regency. This research was conducted from july to september. The type of research used is a survey research type, where samples are taken from one population to be asked for the required data. The results of the study showed (1) clove farming income to household income of Rp. 11,384,386, (2) the contribution of clove farming to household income of farmers in Saibuah Village, Posigadan District, South Bolaang Mongondow Regency of 79.21% obtained from the comparison between the average total income of clove farming of Rp. 11,384,386 minus the average income of farmer households of Rp. 14,371,890 and multiplied by 100%, from the contribution value above it is stated that the contribution of clove farming to household income of farmers in Saibuah Village, Posigadan District, South Bolaang Mongondow Regency provides a very large contribution or >50%. this is because the average value of clove farming income is higher than the average value outside the agricultural sector and outside clove farming.